Report on the occurrence of Haplometroides buccicola (Trematoda, Digenea, Plagiorchiidae) infecting Phalotris lativittatus (Serpentes, Colubridae) in Brazil - Silva, R. J. [UNESP]; Andrade, P. A. [UNESP]; Monteiro E Silva, H. A. [UNESP]; Rossellini, M. [UNESP]; Barrella, T. H. [UNESP] (Centro de Estudos de Venenos e Animais Peçonhentos, 2005)
Haplometroides buccicola (Trematoda, Digenea, Plagiorchiidae) was reported in the mouth and oesophagus of Phalotris lativittatus (Serpentes, Colubridae) from Botucatu, São Paulo State, Brazil. This is the first report on the occurrence of H. buccicola parasitizing P. lativittatus. The Haplometroides genus was also discussed and the most important morphological characters for the identification of the species H. buccicola and H. odhneri are presented.
Keywords: Haplometroides buccicola; Trematoda; Plagiorchiidae; Phalotris lativitattus; Serpentes; Colubridae